Pemanfaatan Chatbot Berbasis AI dalam Sistem Informasi Manajemen Penjualan Mobil - Alfonso Pareandos Sitorus; Darwis Robinson Manalu (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The development of artificial intelligence (AI) technology has had a significant impact on the digital transformation of management information systems (MIS), particularly in the car sales sector. AI-based chatbots have now become an effective solution to address the need for real-time customer service, automate user interactions, and assist in the sales process. Chatbots utilize Natural Language Processing (NLP) to understand and handle consumer requests without direct human intervention. The implementation of this technology in car sales information systems can reduce the workload of sales teams, accelerate responses to customer inquiries, and improve the overall quality of customer service. The collected interaction data can then be utilized by management for analyzing buyer preferences and planning more accurate marketing strategies. This study examines the phenomenon of successful chatbot implementation in various digital sales sectors and maps its potential utilization in the context of car sales. The study results indicate that the integration of AI-based chatbots not only optimizes the customer service process but also enhances operational efficiency and the overall effectiveness of the sales management information system. The implications of this research provide a strong foundation for automotive companies to adopt chatbots as an essential part of their digital sales strategy in the Industry 4.0 era.